Analisis Pengelolaan Keuangan dan Dampaknya terhadap Kepuasan Penghuni: Studi Kasus pada Kost Ungu Bawen - Laia, Rika Farni; Maryani, Tri (Mahesa Research Center, 2025)
This article aims to analyze financial management and its impact on tenant satisfaction at Kost Ungu Bawen. The study focuses on how financial management is implemented, the extent to which it influences tenant satisfaction, and which financial factors are most dominant in improving comfort and perceived value. To address these issues, the study applies cost efficiency theory, micro financial management, and customer satisfaction concepts. Data were collected through in-depth interviews with the owner and tenants, participatory observations of facilities and operational management, and documentation of financial reports and maintenance records, then analyzed qualitatively using a thematic approach. The study concludes that systematic financial management, including cash flow recording, allocation of funds for facility maintenance, cleanliness, and prompt response to complaints, significantly enhances tenant satisfaction. Transparency in fund usage fosters trust and tenant loyalty. The most dominant factors are fund allocation for maintenance and cleanliness, followed by transparency and responsiveness. The findings emphasize that efficient financial management practices can serve both as an operational strategy and a service strategy to improve tenant satisfaction and the competitiveness of medium-scale boarding houses.